2017
DOI: 10.2298/gensr1703865y
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence variability analysis of Major Histocompatibility Complex Class II DQA1 gene in Nigerian goats

Abstract: Wheto and I. G. Imumorin (2017): Nucleotide sequence variability analysis of major histocompatibility complex class II DQA1 gene in Nigerian goats. Vol 49, No.3,[865][866][867][868][869][870][871][872][873][874] Major Histocompatibility Complex (MHC) molecules loaded with peptides derived from invading pathogens are recognised by the immune system to produce a highly effective and specific response against foreign pathogens. A 310-bp fragment of exon 2 of the MHC Class II DQA1 gene was amplified in 27 animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Also, the inclusion of the Luxi Game chicken in the trend illuminates the tendency of alleles to be shared between strains not minding the geographical barrier. This strongly supports the existence of trans-species polymorphism as reported by YAKUBU et al (2017). The result of the phylogenetic tree showed that Normal feathered was more diverse from others.…”
Section: Phylogenetic Analysissupporting
confidence: 89%
“…Also, the inclusion of the Luxi Game chicken in the trend illuminates the tendency of alleles to be shared between strains not minding the geographical barrier. This strongly supports the existence of trans-species polymorphism as reported by YAKUBU et al (2017). The result of the phylogenetic tree showed that Normal feathered was more diverse from others.…”
Section: Phylogenetic Analysissupporting
confidence: 89%